INTELLECTUAL CAPITAL, COMPETITIVE ADVANTAGE (EVIDENCE FROM INDONESIA’S MANUFACTURING SECTOR) - Merida, Peggy Delita (RIMA - Research In Management and Accounting, 2021)
The study aims to examine the direct relationship between intellectual capital and competitive advantage. The contribution of this paper is that there is a proxy competitive advantage the study was conducted on 444 manufacturing companies in Indonesia from 2013-2017. The novelty in this study is a research model that makes competitive advantage a dependent variable for intellectual capital and competitive advantage variables using market share proxy. The result of this study is intellectual capital has a positive effect on competitive advantage.